The Implementation of Waqf as 'Urf in Indonesia - Ani Yumarni; Gemala Dewi; Jaih Mubarok; Wirdyaningsih Wirdyaningsih; Anna Sardiana (Sriwijaya Law Review, 2021)
As a tradition that has been practised for a long time, waqf or endowment is clear evidence that Muslims in Indonesia are developing through this worship. However, what if the waqf is in the form of a mosque, Islamic school, and grave (3Mâ€™s waqf). It is an unusual thing in the contemporary Islamic tradition, but its existence persists. Meanwhile, 'Urf as one of the legal propositions in establishing Islamic law has known the concept and has been practised for generations in suburban areas where most of the population is Muslim. This tradition is then accommodated in Law Number 41 of 2004 concerning endowment, which contains land endowment and endowment organiser (nazhir). This paper examines the tradition of endowment in Indonesian society to benefit mosques, Islamic schools, and graves. By using the historical and analytical-conceptual approaches, this paper will analyse waqf in these three forms. The results of this study can be taken into consideration by stakeholders in developing strategies for strengthening and empowering 3M's donated land to create benefits for the Indonesian since 3Mâ€™s endowment is commonly found in Indonesian society.